2005
DOI: 10.1080/14786410412331280096
|View full text |Cite
|
Sign up to set email alerts
|

Latazienone, a new lathyrane-type diterpenoid fromEuphorbia lataziKunth

Abstract: A new lathyrane-type diterpene 8alpha,15beta-diacetoxy-7beta-benzoyloxy-3beta-(2-methylpropanoyloxy)-4alphaH,9alphaH, 11alphaH-lathyra-5E,12E-dien-14-one (latazienone) has been isolated from the latex of Euphorbia latazi Kunth. The structure of the new diterpene was determined by a combination of ID- and 2D-NMR techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Some of these plants are used in folk medicine in the treatment of skin diseases, ulcers and warts, as well as cancer tumors and intestinal parasites (Hartwell, 1969;Rondón et al, 2005). In the past few years, Euphorbia species have been investigated extensively for the presence of polycyclic and macrocyclic diterpenes, some of which have shown several biological effects such as, antitumor (Valente et al, 2004;Miglietta et al, 2003), cytotoxic (Kong et al, 2002), antiviral (Zheng et al, 1998) and multidrug resistance reversing activity (Duarte et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Some of these plants are used in folk medicine in the treatment of skin diseases, ulcers and warts, as well as cancer tumors and intestinal parasites (Hartwell, 1969;Rondón et al, 2005). In the past few years, Euphorbia species have been investigated extensively for the presence of polycyclic and macrocyclic diterpenes, some of which have shown several biological effects such as, antitumor (Valente et al, 2004;Miglietta et al, 2003), cytotoxic (Kong et al, 2002), antiviral (Zheng et al, 1998) and multidrug resistance reversing activity (Duarte et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…The above functionalities accounted for four degrees of unsaturation, and the remaining three degrees of unsaturation required the presence of three additional rings in the molecule. 13 C-NMR signals at  C 30.7 (C-11), 29.5 (C-9), 29.1 (C-18), 24.4 (C-10), and 16.2 (C-19) indicated a gem-dimethyl-substituted cyclopropane ring, [5][6][7] which was further confirmed by HMBC spectrum (Fig. 2).…”
mentioning
confidence: 58%
“…3) and 13 C-NMR spectra. Since the angular proton H-4 was assumed to be -oriented on a biogenetic basis, 5,[8][9][10][11] the NOESY cross peaks between H-4 and H-1, H 3 -16, H-3, indicated that Me-16 at C-2 was in -configuration and the hydroxyl at C-3 was in -configuration. The absence of a cross peak between H-4 and MeOAc at C-15 supported a trans-fused cyclopentane ring which is usual in other lathyrane derivatives.…”
mentioning
confidence: 99%
“…Although the polyol core with these substituents was previously reported for latazienone (1), the spectroscopic data of 4 were different [3]. Significant differences were found in the coupling values and chemical shifts for protons H-2, H-3 and H-4 indicating the possible presence of an isomer.…”
mentioning
confidence: 69%
“…Lam.) reported the presence of terpenes, specifically a new lathyrane called latazienone (1) and lanosterol, a known triterpene [3]. Subsequent, study of the aerial parts of Euphorbia laurifolia led to the isolation of new lathyrane-type diterpenes, the putative cellular targets of which were investigated following a proteomic approach [4].…”
mentioning
confidence: 99%